AB0657 Genetic and Clinical Predictors of Response to Tnf-Alpha Therapy in an Italian Axial-Spa Cohort. (10th June 2014) - Simone, D.; Canestri, S.; Nowik, M.; Messuti, L.; Miceli, M.C.; Privitera, R.; Gremese, E.; Di Mario, C.; Tolusso, B.; Ferraccioli, G.
Abstract : Background: The genetic background has been demonstrated to be important in the pathogenesis of spondyloarthritides. Several genes besides HLA-B27 have shown to be correlated to the development of several clinical manifestations within the spectrum of spondyloarthritides. It is known that other factors (gender, body mass index) can influence the response to treatments in spondyloarthritis. Objectives: We aimed to evaluate the frequency of the polymorphism of the enhancer HS1, 2A of the Ig Heavy 3' regulatory region, previously described as associated to autoimmune conditions (rheumatoid arthritis, systemic sclerosis, systemic lupus erythematosus), in patients with spondyloarthritis (SpA), and to identify a correlation of this genetic factor to a specific phenotype of the disease or to a different response to therapy. We also aimed to identify other predictors of response to the anti-TNFa treatment among genetic and clinical factors. Methods: We evaluated 153 patients with a diagnosis of axial-SpA according to the 2009 ASAS criteria, of which 125 had differentiated forms (ankylosing spondylitis, psoriatic spondyloarthritis or IBD-associated spondyloarthritis; 77 men, average age 39.6±7.9 years, 77.6% in treatment with anti-TNFa agents and 22.4% at the second treatment) and 28 undifferentiated spondyloarthritis (uSpA) (12 men, average age 42.5±15.7 years, 78.6% treated with anti-TNFa agents) to identify predictors for disease-activity outcome at the last follow up available. BASDAI and ASDAS were used to assess the clinical response. Selective polymerase chain reaction of the region containing polymorphic HS1, 2A alleles was performed on all patients after informed consent [1]. Results: The frequency of 2/2 genotype of the HS1, 2A enhancer was significantly increased in patients with spondyloarthritis compared to healthy controls (40.9% vs 15.7%, p<0.001), especially in those with a differentiated disease, while no difference in frequency was found for the different clinical subtypes of the disease. Considering the predictors of response to treatments, patients needing a switch to a second TNFa blocker were more likely female subjects and not-carriers of HLA B27. The logistic regression analysis showed that patients with higher BMI and of female sex had low response rate in reaching low disease activity (BASDAI<4) [BMI: OR 40, 95%CI (4.2-333.3); sex: OR 142.8, 95%CI (8.9-1000)] and strong clinical response (BASDAI<1) [BMI: OR 7.95%CI (1.6-31.2); sex: OR 1.8, 95%CI (1.1-6.3)] at 12 months follow up from the start of the biological therapy. Considering the average time to reach the clinical remission, female patients, patients with BMI >25 and not-carriers of the 2/2 genotype of HS1, 2A showed to be slower responder to the anti-TNFa. Conclusions: Our data show an association in spondyloarthritis with the allele 2 of the gene enhancer HS1, 2A, similarly for what already observed in other autoimmune diseases (rheumatoid arthritis, systemic sclerosis, systemic lupus erythematosus). We also show that BMI, sex [2] and the presence of a specific polymorphism of gene HS1, 2A might influence the response to the anti-TNFa therapy. References: Tolusso B et al., Ann Rheum Dis 2009. Gremese E et al. J Rheumatol 2014. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4272